Youth engagement in developing an implementation science research agenda on adolescent HIV testing and care linkages in sub-Saharan Africa. (1st July 2017) - Denison, Julie A.; Pettifor, Audrey; Mofenson, Lynne M.; Kasedde, Susan; Marcus, Rebecca; Konayuma, Katongo J.; Koboto, Katlego; Ngcobo, Mmangaliso Luyanda; Ndleleni, Nokuthula; Pulerwitz, Julie; Kerrigan, Deanna
Abstract : Background: The importance of youth engagement in designing, implementing and evaluating programs has garnered more attention as international initiatives seek to address the HIV crisis among this population. Adolescents, however, are not often included in HIV implementation science research and have not had opportunities to contribute to the development of HIV-related research agendas. Project Supporting Operational AIDS Research (SOAR), a United States Agency for International Development-funded global operations research project, involved youth living with HIV in a meeting to develop a strategic implementation science research agenda to improve adolescent HIV care continuum outcomes, including HIV testing and counseling (HTC) and linkage to care. Methods: Project SOAR convened a 2-day meeting of 50 experts, including four youth living with HIV. Participants examined the literature, developed research questions, and voted to prioritize these questions for the implementation science research agenda. This article presents the process of involving youth, how they shaped the course of discussions, and the resulting priority research gaps identified at the meeting. Results: Youth participation influenced working group discussions and the development of the implementation science agenda. Research gaps identified included how to engage vulnerable adolescents, determining the role that stigma, peers, and self-testing have in shaping adolescent HTC behaviors, and examining the costs of different HTC and linkage to care strategies. Conclusion: The meeting participants developed the research agenda to guide future implementation science research to improve HIV outcomes among adolescents in sub-Saharan Africa. This process highlighted the importance of youth in shaping implementation science research agendas and the need for greater youth engagement.